Ameliorative effect of recombinant human lactoferrin on the premature ovarian failure in rats after cyclophosphamide treatments - Shubin Li; Mengnan Liu; Hongmeng Ma; Qin Jin; Yuzhen Ma; Chunyu Wang; Jingyu Ren; Gang Liu; Yanfeng Dai (BMC, 2021)
Abstract This study investigated the effect of recombinant human lactoferrin (rhLF) on the premature ovarian failure (POF) of rats. After cyclophosphamide treatments, the POF rats were divided into the following groups: normal control group (NC), low-dose group (LD), medium-dose group (MD) and high-dose group (HD) of rhLF. After drug administrations, the ovarian indexes and hormonal levels were detected. After follicle number count, the proliferation and apoptosis were analyzed with the expressions of genes related with oogenesis, reactive oxygen species (ROS) production and apoptosis detected, followed by the calculation of oxidative stress and protein expressions. After 4-hydroperoxy cyclophosphamide (4-HC) treatments, the effect of rhLF on the proliferation, ROS production and gene expressions of primary rat granulosa cells (GCs) cultured in vitro were detected. After mating, the fertilities of POF rats were recorded. The result showed that the rhLF administrations up-regulated the ovarian index with the number of developing follicles increased and the decreases of hormonal levels conferred. The Ki-67 intensities of the MD and HD groups were up-regulated with the Tunnel intensities decreased. The rhLF treatments significantly promoted the expression of oogenesis, antioxidant and anti-apoptosis related genes. The expression of Bax and Caspase 3 were decreased with the expression of Bcl-2 up-regulated after rhLF administrations. The in vitro treatments of rhLF effectively conferred the toxicity of 4-HC on primary rat GCs. The fertility assessment showed the rhLF treatments up-regulated the offspring's' folliculogenesis, which confirmed the ameliorative role of rhLF on the POF damages via the inhibition of ROS production in GCs.